Winners, Losers, Insiders, and Outsiders: Comparing Hierometer and Sociometer Theories of Self-Regard - Mahadevan, Nikhila; Gregg, Aiden P.; Sedikides, Constantine; de Waal-Andrews, Wendy G. (Frontiers in Psychology, 2016)
What evolutionary function does self-regard serve? Hierometer theory, introduced here, provides one answer: it helps individuals navigate status hierarchies, which feature zero-sum contests that can be lost as well as won. In particular, self-regard tracks social status to regulate behavioral assertiveness, augmenting or diminishing it to optimize performance in such contests. Hierometer theory also offers a conceptual counterpoint that helps resolve ambiguities in sociometer theory, which offers a complementary account of self-regard’s evolutionary function. In two large-scale cross-sectional studies, we operationalized theoretically relevant variables at three distinct levels of analysis, namely, social (relations: status, inclusion), psychological (self-regard: self-esteem, narcissism), and behavioral (strategy: assertiveness, affiliativeness). Correlational and mediational analyses consistently supported hierometer theory, but offered only mixed support for sociometer theory, including when controlling for confounding constructs (anxiety, depression). We interpret our results in terms of a broader agency-communion framework.